Proceso de atención de enfermería en neonato con asfixia severa. - Grizutti Avilés, Nesvary Devaky (2021)
Below is a clinical case study based on the application of the nursing care process in an RN with severe neonatal asphyxia at the University Hospital of Guayaquil, the same one that was born under unfavorable clinical conditions as a result of a prolonged labor (RN trapped for approximately 45 minutes) from which depressed male product was obtained, hypotonic, hypoactive, with Apgar of 1 minute of life, neonatal asphyxia is a damage that occurs in the newborn due to a pathophysiological interruption in the fetal gas exchange, the approach consists of interventions through positive ventilation to improve cardiopulmonary conditions, during this critical stage that compromised the state of life of the RN it was essential to use the nursing process which provided nursing diagnoses as a pattern ineffective respiratory, deterioration of gas exchange in chronological, systematic order and prioritized interventions, such as using oxygen by nasal cannula, parenteral amino acid nutrition, antibiotic therapy and electrolyte infusion, As a general objective of the study was raised; perform the process of nursing care in neonate with severe asphyxia, and as specific objectives the following criteria were raised: assessment of the general state of the RN, planning of prioritized nursing interventions, measurement of nursing results with follow-up to medical treatment, all these care applied from day 1 of his hospitalization until his epicrisis allowed the prompt progressive recovery of the RN during his hospital instance.